The uses of digital media by Saudi youth and its role in shaping their social awareness (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to explore the role of digital media in shaping the social awareness of Saudi youth, in light of the Kingdom's rapid digital transformation and in line with the goals of Vision 2030, which focuses on empowering youth and enhancing their community participation. The study sought to identify the patterns of digital platform use among Saudi youth (aged 18-34), assess their level of awareness of social issues, and examine the relationship between exposure to these platforms and the formation of their awareness. It also aimed to identify differences attributable to demographic variables (gender, educational attainment, and age).The study's theoretical framework was based on the Uses and Gratifications Theory to explain the motivations of young people in using digital media and the gratifications they derive from it. Methodologically, the study employed a descriptive-analytical approach using a survey sampling method. The data collection instrument was a questionnaire designed to measure the study variables and verify its psychometric properties (validity and reliability). The study was conducted on a convenience sample of 384 young Saudis.The importance of this study lies in providing a cognitive and applied framework that helps decision-makers and media and educational institutions to understand the new dynamics of shaping social awareness in the digital space, which contributes to developing strategies that promote the positive use of these platforms in a way that serves national identity and social values.
Keywords: Saudi Youth; Digital Media; Social Awareness